2021
DOI: 10.1182/bloodadvances.2021004530
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model (BATAP) with external validation for patients with transplant-associated thrombotic microangiopathy

Abstract: Transplant-associated thrombotic microangiopathy (TA-TMA) is a potentially life-threatening complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Information on markers for early prognostication remains limited, and no predictive tools for TA-TMA are available. We attempt to develop and validate a prognostic model for TA-TMA. A total of 507 patients who developed TA-TMA following allo-HSCT were retrospectively identified and separated into a derivation cohort and a validation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(176 reference statements)
0
7
0
Order By: Relevance
“…Most of the patients received haploidentical stem cell transplantation. The conditional regimen for these patients was mainly a strategy of modified busulfan/cyclophosphamide and anti‐thymoglobulin (ATG), details were reported in our previously published articles 11–13 . The HLA‐matched recipients mostly received modified BU/CY regimen without ATG.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the patients received haploidentical stem cell transplantation. The conditional regimen for these patients was mainly a strategy of modified busulfan/cyclophosphamide and anti‐thymoglobulin (ATG), details were reported in our previously published articles 11–13 . The HLA‐matched recipients mostly received modified BU/CY regimen without ATG.…”
Section: Methodsmentioning
confidence: 99%
“…The source of hematopoietic stem cells was mostly peripheral blood stem cells and bone marrow stem cells, which were harvested in accordance with the protocol established by our institute 13 . GVHD prophylaxis strategy consists of short‐term MTX, mycophenolate and CsA 11,14 . Prophylaxis practices for GVHD and HZ remained consistent and comparable from 2012 to 2017.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported prognostic implications of sC5b-9 including (1) values ≥ 244 ng/dl at the time of diagnosis ( 2 ); (2) a change in level of 1.8-fold from baseline to diagnosis ( 51 ); (3) an increase of a log at the time of TA-TMA ( 51 ); and (4) levels of sC5b-9 ≥300 ng/l and ANG-2 > 3000 pg/ml in patients with concurrent TA-TMA and GVHD ( 36 ). Markers of microangiopathy including decreased levels of haptoglobin ( 52 ), elevated levels of LDH ( 15 , 53 ), and scores that use laboratory values of microangiopathy, including BATAP (bilirubin, age, thrombocytopenia, anemia, proteinuria) ( 54 ) TMA index (LDH/platelets), and an EASIX score ( 55 ), all portended a poor prognosis. also portended a poor prognosis ( 14 ).…”
Section: Resultsmentioning
confidence: 99%